SAT0193 A PHASE 3, OPEN-LABEL, CONTINUATION STUDY EVALUATING LONG-TERM SAFETY AND EFFICACY OF BELIMUMAB IN PATIENTS FROM JAPAN AND KOREA WITH SYSTEMIC LUPUS ERYTHEMATOSUS, FOR UP TO 7 YEARS. (2nd June 2020) - Tanaka, Y.; Bae, S. C.; Bass, D.; Chu, M.; Curtis, P.; Derose, K.; Ji, B.; Kurrasch, R.; Lowe, J.; Meizlik, P.; Roth, D.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disorder more prevalent in the Asian population vs Caucasians. Belimumab (BEL), a monoclonal antibody targeting B-lymphocyte stimulator, is approved in patients (pts) ≥5 years with active, autoantibody-positive SLE. Objectives: Evaluate long-term safety and efficacy of intravenous (IV) BEL + standard SLE therapy (SST) in pts with SLE in Japan/Korea. Methods: In this Phase 3, multicentre, open-label (OL) study (BEL114333; NCT01597622 ), eligible (≥18 years of age) completers of the double-blind phase of GSK study BEL113750 in Japan and South Korea or the subcutaneous OL phase of GSK Study BEL112341 in Japan, received monthly BEL 10 mg/kg IV plus SST. Primary endpoints: safety assessments. Key secondary endpoints: SRI4 response rate at each scheduled visit (observed data), defined as a ≥4-point reduction from baseline in SELENA-SLEDAI score, no worsening in PGA (<0.3-point increase from baseline) and no new BILAG 1A/2B organ domain scores; time to first severe SFI flare over time. Endpoints were analysed relative to first BEL dose (parent or current study). No follow-up data were collected after study withdrawal. Results: Overall, 142 pts were enrolled (Japan n=72; Korea n=70), 104 (73.2%) completed the study, 1 (0.7%) died and 37 (26.1%) withdrew. Overall, 139 (97.9%) pts had ≥1 adverse event (AE) (Table ). Most frequent AEs included: nasopharyngitis (60.6%); headache (28.2%); cough, herpes zoster and viral upper respiratory tract infection (18.3% each). Serious AEs (SAEs) occurred in 48 (33.8%) pts. Most common SAEs were infections and infestations, reported in 24 (16.9%) pts (Table ). During this study, the annual incidence of AEs, including SAEs and AESI, remained stable or declined, with no trends of clinical concerns regarding the incidence of Grade 3 or 4 values for laboratory parameters. There was 1 transient positive immunogenicity result of no clinical concern. The proportion of SRI4 responders was 47.8% at Year 1 (Week 24) and tended to increase numerically up to 84.6% at Year 7 (Week 48). The proportion of pts with a ≥4-point decrease from baseline in SELENA-SLEDAI score numerically increased from 51.5% at Year 1 (Week 24) to 84.6% at Year 7 (Week 48). Proportion of pts with no PGA worsening was 91.3-100% and the proportion with no new BILAG 1A/2B organ domain scores was 93.3-100% up to Year 7 (Week 48). A total of 21 (14.8%) pts had 24 severe SFI flares. Conclusion: BEL was well tolerated as add-on therapy to SST for ≤7 years in pts with SLE from Japan/Korea. Safety results were consistent with the known BEL safety profile. Study funding: GSK. Disclosure of Interests: Yoshiya Tanaka Grant/research support from: Received research grants from Asahi-Kasei, Mitsubishi-Tanabe, Chugai, Takeda, Sanofi, Bristol-Myers, UCB, Daiichi-Sankyo, Eisai, Ono, Speakers bureau: Received speaking fees and/or honoraria from Daiichi-Sankyo, Astellas, Chugai, Eli Lilly, Pfizer, AbbVie, YL Biologics, Bristol-Myers, Takeda, Mitsubishi-Tanabe, Novartis, Eisai, Janssen, Teijin, Sang-Cheol Bae: None declared, Damon Bass Shareholder of: GSK, Employee of: GSK, Myron Chu Shareholder of: GSK, Employee of: GSK, Paula Curtis Shareholder of: GSK, Employee of: GSK, Kathleen DeRose Shareholder of: GSK, Employee of: GSK, Beulah Ji Shareholder of: GSK, Employee of: GSK, Regina Kurrasch Shareholder of: GSK, Employee of: GSK, Jenny Lowe Shareholder of: GSK, Employee of: GSK, Paige Meizlik Shareholder of: GSK, Employee of: GSK, David Roth Shareholder of: GSK, Employee of: GSK